Scleral Fixation of Intraocular Lens - Wasif M Qadri, Zia ul Mazhri (Pakistan Journal of Ophthalmology, 2008)
Purpose: Evaluation of a simplified technique of scleral fixation of posterior chamber IOL in terms of visual outcome and complications. Material and Methods: Fifty eyes of 48 patients with sclerally fixated IOL were included in the study. In general these eyes were lacking adequate posterior capsular (PC) support for routine posterior chamber intraocular lens implantation. 9/0 Nylon (Ethicon), 10/0 polypropylene(Proline) and occasionally 10/0 Nylon were the sutures used for transscleral fixation of the lens heptics. Transscleral suture passage was performed with Ab Externo Cum Ab Interno Technique in 21 patients and modified Ab Externo Technique in 29 patients Anterior core vitrectomy was performed as a routine accompaniment. The follow up ranged from 8-36 months and average follow up was 21.4 months. Results: Visual outcome was quite good. Average visual acuity was in the range of 6/9-6/12, which is quite comparable to other kinds of implantations. The most common complication was vitreous hemorrhage and hyphaema, which resolved in all the patients with no residual complications. Conclusion: Scleral fixation of IOL is an effective but surgically demanding technique. There is no reason to become somewhat over conscious about the slightly higher risk of complications with scleral-sutured PC IOL. Most of these complications can be avoided or minimized by proper selections of materials used and adopting the proper technique.